EFEKTIVITAS PELAKSANAAN PROGRAM AYO NABUNG SAMPAH DALAM MENJAGA DAN MEMELIHARA KEBERSIHAN LINGKUNGAN DI KECAMATAN MAESA KOTA BITUNG - PUTRI, AYUNDA; LENGKONG, FLORENCE DAICY; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2018)
The aims of this research is to examine the effectiveness of implementation Ayo Nabung Sampah program in maintaining environmental cleanliness in the subdistrict of Maesa the city of Bitung. This research use descriptive qualitative approach with theory of effectiveness by Sondang Siagian (2000). The informants of this research are the parties involved in the implementation of the Ayo Nabung Sampah program in Maesa subdistrict. The collection techniques used interviews and documentation and the data analyzed can be done by data reduction, data presentation, and resulting the conclution of the data. The results showed that the Ayo Nabung Sampah program already operating effectively enough. It can be seen from the clarity of objectives to be achieved, goal achievement strategy, analysis process and the steady policy formulation, good planning, preparation of appropriate programs, and the availability of infrastructure. However, there are still two imdicator are didn’t optimal, that is goal achievement strategy, the strategies used in this case are socialization and promotion, the socialization and promotion carried out are not optimal because the mindset and behavior of the society are not able tp be changed. the socialization and promotion carried out are not optimal is also impact on not understanding the society and also external parties regarding the purpose of this program. And the second indicator is the availability of infrastructure in Kekenturan Satu Urban village are still did’t optimal. Keywords: Effectiveness, Ayo Nabung Sampah program